Analisis Kesiapsiagaan Desa Siaga Api di Desa Pantai Beringin, Kecamatan Sulamu, Kabupaten Kupang - Kristoforus Son; Ludji Michael Riwu Kaho; Norman Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
In general, forest fires in Indonesia cause by three main factors, namely fuel condition, weather and social cultural of the community. Forest and land fires (Karhutla) can cause negative impact to the environtment, public health and economy. East Nusa Tenggara (NTT) is a province that often experience severe forest and land fires, including that happened in Pantai Beringin Village. One of the effort to overcome this problem is to form “Masyarakat Peduli Api” (MPA) despite it has been formed, forest and land fires still occured in Pantai Beringin Village every year. The research area take place in Pantai Beringin Village, Sulamu District, Kupang Regency with total area of 3048 ha. This research carried out to determine preparedness of Pantai Beringin Village to face the land and fires.Tthis research done on March-April 2022. Respondent in this study consisted of 50 person. Respondents were obtained using purposive sampling method and Slovin formula, and analyzed using descriptive and quantitative analysis methods using the Village Alertness Index Formula (IKD). The results of the research obtained through interview method with the help of questionnaires and direct observation method show that the alertness of pantai beringin village to the forest and land fires can be categorized of Class D (Low), because characterized by very active community, involvement, real functioning fire control teams, infrastructure, livelihoods still dependent on fire, and lack of support from the village government.